Paradigma Ekonomi Islam Terhadap Konsep Marketing: Kajian Teori dan Penerapan Ekonomi Islam dalam Kegiatan Pemasaran - Fahrurrozi (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Marketing is not only known as a practical element but marketing is also known as one of the disciplines. The fact that it continues to play an important role in corporate strategy in some companies indicate that there is an opportunity and took a real approach to building marketing competence as a source of competitive advantage. business practices and marketing is currently experiencing a shift or transformation of the intellectual level (rational), the emotional, spiritual, and finally to the spiritual. The difference between the paradigm in the conventional marketing activities with Islam is very clear, which is based on the conventional marketing behaviors that occur in economic units is not the limitation of the Shari'a. Conversely in Islamic marketing behaviors in economic activity is limited by the provisions of Shari'ah that its implementation is guided by morals. The purpose of this study to know to know marketing in an economic paradigm of Islam as well as to determine the application of marketing concepts in the view of Islamic economics. This study uses a qualitative method while the data used are secondary data obtained with books, journals, and other of scientific works. This research uses the study of literature and using descriptive analysis. The results of the analysis explains that the marketing paradigm in Islamic economics promoting the common good and mutually beneficial (symbiotic motualisme) certainly adhering to the teachings of Shariah. And the fundamental difference between conventional marketing syar'iah marketing lies in the values ​​espoused by the marketer (the marketer).